Design of Hazardous Waste Station in XYZ Port, Jakarta City - Wibisono, Andhika Yoga; Kusumaningtyas, Disfiatri; Lahmadi, Salman Farid; Najwa, Alfiyah; Rachmantoro, Hafiz Arie; Sarwono, Ariyanti; Suryawan, I Wayan Koko (Fakultas Teknik UB, 2020)
The design of the hazardous waste station is intended to adjust the security in the XYZ port area based on the fire and leakage possibility based on hazardous waste generation. The research method uses primary data, which is the measurements to determine the availability of land area, and secondary data to determine the generation amount and solid waste characteristics. The design of the hazardous waste station began with field observations to measure the land availability, then collected secondary data to know the volume type, volume, characteristics, and dimensions of hazardous waste collection. The composition of hazardous wastes based on the solid waste characteristics is flammable (20%), flammable and toxic (56%), toxic (23%), and corrosive (1%). The result found that the recommended dimension of the hazardous waste station is 11m x 8m.Â The total area of ventilation needed is 8m2. The light source of a hazardous waste station is recommended to have 40 Watts of power and each Armature has 2 lights. The container dimensions for leakage prevention are 2m x 2m x 0.6 m with a freeboard of 0.3 m. The fire extinguisher with a range of 12 m